2009
DOI: 10.1007/s11816-009-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and simple method for DNA extraction from plant and algal species suitable for PCR amplification using a chelating resin Chelex 100

Abstract: A DNA extraction method using Chelex 100 is widely used for bacteria, Chlamydomonas, and animal cell lines, but only rarely for plant materials due to the need for additional time-consuming and tedious steps. We have modified the Chelex 100 protocol and successfully developed a rapid and simple method of DNA extraction for efficient PCR-based detection of transgenes from a variety of transgenic plant and algal species. Our protocol consists of homogenizing plant tissue with a pestle, boiling the homogenized ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Moreover, a genetic characterization using bio-molecular tools were applied to plant fresh material in order to confirm genus and species identification. Briefly, DNA from Scabiosa stems, freshly collected was extracted using the chelating resin Chelex 100 [ 52 ]. The extraction eluate was subjected to a polymerase chain reaction (PCR) amplification of a Chloroplastic DNA fragment, using the species- and group-specific primers “ycf6F” and “psbMR”, targeting for the petN-psbM intergenic spacer region [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a genetic characterization using bio-molecular tools were applied to plant fresh material in order to confirm genus and species identification. Briefly, DNA from Scabiosa stems, freshly collected was extracted using the chelating resin Chelex 100 [ 52 ]. The extraction eluate was subjected to a polymerase chain reaction (PCR) amplification of a Chloroplastic DNA fragment, using the species- and group-specific primers “ycf6F” and “psbMR”, targeting for the petN-psbM intergenic spacer region [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Modifications of the DNA extraction using Chelex-100 [ 14 ] involve additional mechanical homogenization for higher plants [ 29 ] or high temperature incubation in ethanol following homogenization for Chlamydomonas reinhardtii and Arabidopsis thaliana [ 30 ]. The protocol presented here dispenses with these procedures, involves fewer steps and equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this technique has been known for almost 30 years (Singer-Sam et al 1989), is commonly used in human forensics (Walsh et al 1991) and has also been successfully used in other eukaryotes (e.g. Pedersen et al 2006;HwangBo et al 2010), this study appears to be the first time it has been reported for use in lichen-forming and lichenicolous fungi.…”
Section: Collection Nomentioning
confidence: 92%
“…It has been successfully applied in a wide range of eukaryotic organisms (e.g. Pedersen et al 2006; Strange et al 2009; HwangBo et al 2010; Casquet et al 2012) including some non-lichenized fungi (e.g. Zhang et al 2010; Turan et al 2015).…”
mentioning
confidence: 99%